Ixazomib – the first oral proteasome inhibitor. Issue 3 (23rd February 2019) - Xie, Jingmei; Wan, Ning; Liang, Zhuoru; Zhang, Tiantian; Jiang, Jie
Abstract: Ixazomib, as a proteasome inhibitor, inhibits the chymotrypsin-like activity of the β5 subunit of the 20S proteasome. Based on the TOURMALINE-MM1 study, ixazomib was proved by the FDA as the orphan drug in November 2015. With a promising effect in prolonging the progression-free survival compared with placebo treatment (median: 20.6 versus 14.7 months), it was the first oral compound combined with lenalidomide and dexamethasone for the treatment of patients with relapsed/refractory multiple myeloma (RRMM) who have received at least one prior therapy. The main adverse events include low-grade hematological, digestive, or cutaneous events, which were manageable with care. Overall, ixazomib demonstrated favorable safety profile. Ongoing trials are conducted to define its place in first-line, maintenance, and relapse therapies. In this review, we summarized the clinical pharmacology, efficacy, tolerability, safety, and cost-effectiveness of ixazomib.